Transformasi Sampah Organik dan Minyak Jelantah sebagai Wujud Kepedulian Lingkungan dan Upaya Peningkatan Pendapatan Masyarakat Desa Bolon - Subiyantoro, Slamet; Safitri, Dila; Sari, Ratih Gusti Permata; Illahi, Adhi Zakiah Nur; Fadhila, Dhea Rizki Nur; Putri, Virda Maulidyah; Setiawati, Stevany Ratna; Pratiwi, Tara; Atikah, Esti; Jati, Rafi’i Waluyo; Widyastoro, Ridho (Yayasan Daarul Huda Kruengmane, 2024)
Management of household waste, especially organic waste and used cooking oil, is one of the environmental challenges faced by many villages in Indonesia. Organic waste that is not managed properly has the potential to pollute the environment, attract pests and contribute to greenhouse gas emissions. Apart from that, used cooking oil that is thrown away carelessly can pollute the air and soil. The article aims to discuss the implementation of organic waste management through biopores and training on processing used cooking oil into aromatherapy candles carried out by KKN students from Sebelas Maret University (UNS) in Bolon Village, Colomadu District, Karanganyar Regency. This program has the potential to reduce the volume of waste, increase environmental awareness, and provide added economic value for village communities.